(3fSH bQjTs - (3GdRHjQj , eUYH Hf YHO Gddg Hf eUYH Hf KGHJ Hf YHO Gddg Hf GdRHjQ, CHh YHO Gddg,J (B236 (3g` s ((3YHO GdgGOi Hf GdgGTei Hf Ydi s)
(3ChdgG (B:s
(3CNHQfG eMeO Hf gOhjJ (B(2) (3Hf YHO GdQMef Hf eYGhjI eYO Hf YOfGf Hf COO Hf Gdge(Bd(3Y s
(3BNQgG (B:s
(3bJd cQR gPG eY QShd Gddg Udi Gddg Ydjg hSde jhe aJM ecI gPg BNQ LegQI bQT hGdMeO ddg cKjQkG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B248 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B291s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs